Les paradoxes de la politisation dans la fonction publique - Jean-Philippe Luis (Mélanges de la Casa de Velázquez, 2005)
The state employees constitute an important part of the elites and middle class of Spain. They are early affected by the liberalism. But this liberalism is not only an ideological posture. It represents the reaction to the absolutism attacks of Ferdinand VII. The universe and values of the state functionary was still rules by the notions prevailing before 1808 and the state employees don’t accept the purges. After, they were very desapointed with the liberal state, which consider job insecurity as a norm. The result of this politic is a limitation of the traditional endogamy which affect the administration.